RANCANG BANGUN ALAT PENDETEKSI DINI GEMPA BUMI MENGGUNAKAN MODUL NODEMCU BERBASIS IOT - Sandy Yustisio Okta Viandra; Joni Maulindar; Harsanto (Jurnal Teknik SILITEK, 2024)
Earthquakes are one of the most common disasters in Indonesia. Earthquakes occur when the earth vibrates or shakes releasing the elastic strain energy of rocks by the activity of shifting earth plates. Earthquakes have various adverse effects, namely damage or destruction, and even casualties. In an effort to increase awareness and minimize victims of earthquakes, a tool is needed to provide warnings and detect the occurrence of an earthquake. In this study, a prototype was made to detect earthquakes by utilizing WhatsApp message notifications. This prototype uses several modules such as, arduino nano, ESP8266, SW 420 vibration sensor, ADXL335 Accelerometer Sensor, Buzzer and LED. The ADXL335 accelerometer sensor detects vibration and acceleration direction and the SW 420 vibration sensor detects a vibration which then the data will be received and processed by Arduino UNO and the results of the data calculation will be forwarded to ESP8266 which will later be sent via WhatsApp. When a vibration or earthquake occurs, the buzzer will sound and the LED will light up. The serial monitor display will show the direction of the earthquake and the magnitude of the earthquake. The result of this research is a prototype of earthquake early warning and detection with the concept of IoT (Internet of Thing). This tool or system will be a conceptual prototype. The making of this tool or system is an effort to anticipate victims of earthquakes and as a way to prevent earthquakes.